Mechanism of root growth and promotion of nodulation in vegetable soybean by Azospirillum Brasilense - Molla, Abul Hossain; Shamsuddin, Zulkifli H.; Mohd. Saud, Halimi (Taylor and Francis Group, 2001)
Stimulation of root growth and promotion of nodulation in vegetable soybean (Glycine max) by Azospirillum brasilense was studied under lightroom conditions to understand the possible mechanism of root growth as well as the enhancement of nodule initiation when co-inoculated with Bradyrhizobium. Root growth stimulation of vegetable soybean was positively influenced by the cell-free supernatant of Azospirillum brasilense Sp7 as well as Sp7 itself, and by indole acetic acid (IAA) application. The cell-free supernatant of Sp7 treated plants produced the highest number of roots and root length plant-1 followed by bacterial cells of Sp7 and IAA log109M) application. Control plants were the lowest. The cell-free supernatant of Sp7 may contain growth stimulants similar to IAA, which was responsible for enhanced root growth. Nitrite and nitrate did not show positive role in increasing root growth in vegetable soybean. Co-inoculation of Azospirillum with Bradyrhizobium significantly (P < 0.05) promoted nodulation in vegetable soybean. Bradyrhizobium strain UPMR48 performed superior role on promotion of nodule growth by co-inoculation to the strain TAL102. Azospirillum has the potential as a coinoculant with Bradyrhizobium in vegetable soybean cultivation.